Association between breast cancer and thyroid cancer: A study based on 13 978 patients with breast cancer. (27th November 2018) - Huang, Nai‐si; Chen, Xing‐xing; Wei, Wen‐jun; Mo, Miao; Chen, Jia‐ying; Ma, Ben; Yang, Shu‐wen; Xu, Wei‐bo; Wu, Jiong; Ji, Qing‐hai; Guo, Xiao‐mao; Liu, Guang‐yu; et al.
Abstract: Background: Thyroid cancer (TC) is one of the most commonly seen secondary malignancy in breast cancer (BC) survivors. Materials and methods: A retrospective study was conducted in BC patients in our center from 1999 to 2013. Patients were divided into BC‐TC group and BC‐alone group. Results: In total, 13 978 BC patients were identified, among whom 247 (1.8%) had TC. The standardized incidence ratio (SIR) of TC was 4.48 compared with Chinese females, and up to 98.0% of cases were thyroid papillary carcinomas. A family history of malignancy was the only independent risk factor (odds ratio = 1.457, P  = 0.025) for development of TC in patients with BC. We also identified inferior survival in patients with synchronous versus metachronous BC‐TC ( P  = 0.016). Synchronous BC‐TC (risk ratio = 5.597, P  = 0.018) was an independent prognostic factor for inferior RFS. Conclusions: We observed high co‐occurrence of TC in patients with BC. There might be different mechanisms behind synchronous and metachronous BC‐TC. Abstract : In the current study, we investigated the association of thyroid cancer incidence in a cohort of 13 978 breast cancer patients. We identified that the standardized incidence ratio of secondary thyroid cancer was significantly increased and a family history of malignancy was the only independent risk factor, which provided a new insight into the association of breast cancer and thyroid cancer.